Analisis Faktor yang Memengaruhi Peningkatan Pendapatan Usaha Petani Bawang Merah di Kabupaten Kolaka Utara - Ngali, Napsiah; Suryanto; Yumna (Perkumpulan Dosen Muda (PDM) Bengkulu, 2025)
This study aims to analyze the factors that affect the income of shallot farming in North Kolaka Regency. The independent variables studied included farmer experience (LN_X1), amount of fertilizer (LN_X2), land area (LN_X3), and labor (LN_X4), while dependent variables were shallot farming income (LN_Y). Cobb-Douglas production function methods and multiple linear regression were used to analyze the data with the help of SPSS 27. The results of the analysis showed that the four independent variables had a significant influence on farming's income simultaneously, with an F value of 658.017 and a significance of 0.000. The land area variable had the greatest partial influence, with a coefficient of 1.385 and a significance of 0.000, while the variables of labor and fertilizer had a positive influence, with significance of 0.014 and 0.038, respectively. However, the farmer's experience did not affect income (significance 0.374). A coefficient of determination (R2) of 0.989 indicates that the model can explain 98.9% of income variations. Other factors outside the model affect the rest of the variation. The results show that increasing the income of shallot farmers can be achieved through the efficient use of input, as well as the strategic role of land access and labor.